Satisfação e estresse ocupacional da equipe de enfermagem de Serviços de Atendimento Móvel de Urgência - Papa, Marília Angelina Ferreira (2013)
Current quantitative, correlational, cross-sectional and descriptive research investigates the satisfaction and occupational stress of the nursing staff of the Mobile Emergency Service (SAMU). Fifty-five nurses from two SAMU units in the state of Paraná, Brazil, participated in the Work Satisfaction Scale (EST) and in Stress Inventory for Nurses (IEE) during May 2013. Data were compiled in databases using Microsoft Office Excel ® 2007 and spreadsheets were later imported to the Statistical Analysis System SAS 9.0 for descriptive and inferential statistics (nonparametric tests). Results showed that publications on occupational stress in nursing staff working in Pre-Hospital Care Mobile units in the last ten years indicated that professionals considered occupational stress experienced in their daily work as specific to the environment in which they lived. They even suggested some measures to minimize it, such as more investment in updating knowledge/staff training on the subject and more institutional appreciation with regard to workers´ health. In the case of SAMU nursing professionals, 87.27% were satisfied, especially with regard to the nature of the work, to colleagues and to managers, even though there were restrictions to promotions and salary. Regarding causes of stress, the professionals highlighted factors intrinsic to the work and career roles. SAMU I nursing professionals were more satisfied with salary (p<0.0001) and overall job satisfaction (p=0.003) when compared to those of SAMU II. In spite of occupational stress reaching 83.63% of professionals, the nursing staff was satisfied with the environment. It may be concluded that there was a significant and negative correlation (p=0.02) between job satisfaction and occupational stress among the services. In other words, professionals who reported dissatisfaction with the job, were also reported stressed. Based on the results, it was necessary that more research work on stress causes was undertaken within the teaching and practice fields and that more discussions between managers and professionals took place on determining factors of satisfaction and occupational stress to improve the physical and organizational conditions in workers´ health, professional performance and service quality.